2022
DOI: 10.1097/phm.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hybrid-Virtual Teaching Model on the Physical Examination Skills of Fourth-Year Medical Students

Abstract: A required fourth-year advanced core neurology-physical medicine and rehabilitation clerkship was adapted to hybrid format (2-wk remote; 2-wk in-person) during the COVID-19 pandemic. With teaching of the neurological physical examination being shifted to the remote component, we sought to determine whether this negatively affected student performance on an Objective Structured Clinical Examination, particularly the physical examination component. Mean pandemic-era total Objective Structured Clinical Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Since the advent of COVID-19 pandemic, there has been several articles on medical student education using electronic or online platforms, 1 barriers and impact faced by hybrid virtual teaching in medical student education, 2,3,4 and hybrid model for organising scienti c events. 5 Notably, many di culties were faced by medical education during the pandemic such as lack of social interactions and impact on educators who are required to learn new skills to engage students and manipulate the electronic platform.…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of COVID-19 pandemic, there has been several articles on medical student education using electronic or online platforms, 1 barriers and impact faced by hybrid virtual teaching in medical student education, 2,3,4 and hybrid model for organising scienti c events. 5 Notably, many di culties were faced by medical education during the pandemic such as lack of social interactions and impact on educators who are required to learn new skills to engage students and manipulate the electronic platform.…”
Section: Introductionmentioning
confidence: 99%
“…The literature [11] suggested that students should master and apply sports knowledge and motor skills to improve their athletic ability, so they should watch sports matches frequently and be able to briefly analyze the phenomena and problems in sports matches to improve their ability to analyze and solve problems. Using research methods such as the literature method, the literature [12] mainly studied the application principles of online and offline hybrid physical education. The literature [13] used the literature method and logical analysis to briefly describe the concept, characteristics and problems of virtual technology as well as the advantages, application areas and impacts of VR+ physical education, to explore the application scenarios of virtual technology in physical education, and finally generalized and sorted out four application strategies, aiming to provide a reference for future scholars' research.…”
Section: Introductionmentioning
confidence: 99%